2012
DOI: 10.3113/fai.2012.0870
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Evaluation of the Normal Distal Tibiofibular Syndesmosis

Abstract: Our data form the basis for revised radiographic criteria to evaluate the distal tibiofibular syndesmosis which may influence clinical management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 20 publications
2
84
0
6
Order By: Relevance
“…Previous studies have found great variability in the radiographic measurements in normal syndesmosis,41 42 and MRI studies have demonstrated that the tibiofibular clear space and tibiofibular overlap measurements on radiographs—measurements that are often used to determine instability—did not correlate with syndesmotic ligament injuries 43 44. MRI has been shown to be accurate in identifying a rupture of one or more of the ligaments 45 46.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found great variability in the radiographic measurements in normal syndesmosis,41 42 and MRI studies have demonstrated that the tibiofibular clear space and tibiofibular overlap measurements on radiographs—measurements that are often used to determine instability—did not correlate with syndesmotic ligament injuries 43 44. MRI has been shown to be accurate in identifying a rupture of one or more of the ligaments 45 46.…”
Section: Discussionmentioning
confidence: 99%
“…55 Recent studies have found great variability in the radiographic measurements of normal patients. 54,56 A study in patients without known clinical or radiographic evidence of abnormality found that the mean TFCS was 4.6 mm on the AP view and 4.3 mm on the mortise view, whereas the mean TFO was 8.3 mm on the AP view and 3.5 mm on the mortise view. It was also demonstrated that a lack of overlap on the mortise view may represent a normal variant.…”
Section: Initial Radiographic Evaluationmentioning
confidence: 97%
“…It was also demonstrated that a lack of overlap on the mortise view may represent a normal variant. 56 MRI studies have demonstrated that the TCFS and TFO did not correlate with syndesmotic injury, and MCS greater External rotation stress test for evaluation of a syndesmotic injury. One hand is placed at the mid-calf to stabilize the leg.…”
Section: Initial Radiographic Evaluationmentioning
confidence: 97%
See 1 more Smart Citation
“…If the contralateral ankle is uninjured, comparison radiographic views should be obtained; comparison of the injured and uninjured ankles is more effective than comparing the injured ankle with standards based on the general population. 20 These views can be obtained with fluoroscopy at the beginning of the surgical procedure, using standard ankle and C-arm positioning. In addition to determining whether an injury is present, these images aid in the assessment of intraoperative reduction.…”
Section: Intraoperative Injury Assessmentmentioning
confidence: 99%